Artificial seawater for seaweed culture - Kaladharan, P (Indian Journal of Fisheries, 2011)
Artificial seawater prepared with simplified recipes was found suitable for maintaining seaweeds of commercial importance under laboratory conditions. The suitability of this artificial seawater formulation studied by gain or loss of wet weight of seaweeds incubated, showed 15.5% increase in specific growth rate in the case of Gracilaria corticata and 18% increase in the case of Ulva lactuca. However, Gracilaria edulis showed 14% decrease over the control. Physicochemical characteristics of artificial seawater were compared with these of natural seawater.